Export cartel and consumer welfare - Mukherjee, Arijit; Sinha, Uday Bhanu (Wiley, 2018)
The purpose of this paper is to show that export cartels are not necessarily harmful for consumers in the importing countries. Using the strategic trade policy model of Brander and Spencer (1985a), we show that, contrary to the harmful effect, product-market cooperation benefits consumers by affecting the trade policies. We further show that consumers in the importing countries are affected adversely if cooperation is among the governments of the exporting countries, instead of the exporting firms.